Tinjauan Iklan Running Text Dan Banner Di Media Televisi - Handriyotopo Handriyotopo (Institut Seni Indonesia Surakarta, 2004)
When television world in Indonesia sprout, what is being happened by station of television have competition display the its pre-eminent event each. Audience TV now only by using remote control can enjoy the event more than 12 channels of television stations. And only with the second calculation can go to the channel as desiring of where he likes. Becoming problem when event break for the advertisement of to most audience TV will remove the its channel to other station. This matter will apprehend the advertiser company causing is not effective is hour display the the advertisement and will cause downhill it their omset. All marketing of consumer product will be made confused as respects to that. Conscious of the situation hence emerge. The advertisement of banner and running texts to support the campaign advertisement the core important and boost up the number sale in consequence audience forced to see to display the though message submitted by very limited.Keyword: running text, banner, hard selling, channel, remote control